Microbial community dynamics during aerobic granulation in a sequencing batch reactor (SBR) - Gómez-Basurto, Fabiola (PeerJ, 2019)
Microorganisms in aerobic granules formed in sequencing batch reactors (SBR) remove contaminants, such as xenobiotics or dyes, from wastewater. The granules, however, are not stable over time, decreasing the removal of the pollutant. A better understanding of the granule formation and the dynamics of the microorganisms involved will help to optimize the removal of contaminants from wastewater in a SBR. Sequencing the 16S rRNA gene and internal transcribed spacer PCR amplicons revealed that during the acclimation phase the relative abundance of Acinetobacter reached 70.8%. At the start of the granulation phase the relative abundance of Agrobacterium reached 35.9% and that of Dipodascus 89.7% during the mature granule phase. Fluffy granules were detected on day 43. The granules with filamentous overgrowth were not stable and they lysed on day 46 resulting in biomass wash-out. It was found that the reactor operation strategy resulted in stable aerobic granules for 46 days. As the reactor operations remained the same from the mature granule phase to the end of the experiment, the disintegration of the granules after day 46 was due to changes in the microbial community structure and not by the reactor operation.